THE CONCEPT OF ISLAMIC EDUCATION ACCORDING TO IBN KHALDUN - Suandi; Herman (Darul Ilmi Bina Insan Foundation, 2024)
This article aims to explore the concept of Islamic education according to Ibn Khaldun. It includes an overview of his biography, his intellectual style, and his works. Additionally, it delves into his definition and objectives of Islamic education, examining the methods and curriculum he proposed. The paper also discusses the relevance and application of Ibn Khaldun's educational concepts in the contemporary era. This research uses a qualitative library research method with a descriptive approach to analyze the concept of Islamic education according to Ibnu Khaldun theoretically and practically. The data analysis technique is by reviewing various literature that is relevant to the concept of Islamic education according to Ibnu Khaldun. The results of the research show that Ibnu Khaldun was one of the Muslim intellectual figures who had a big influence on the development of science and the progress of the world of education at that time. The concept of Islamic education uses a philosophical and empirical approach in formulating the ideal and practical vision, mission, goals, and targets of Islamic education. Islamic education is a vehicle for producing quality human resources (HR). Islamic education is also the biggest investment in developing knowledge, creating jobs, and the ability to adapt to the times and global challenges. The concept of Islamic education initiated by Ibnu Khaldun remains relevant today, even though he lived in the 14th century AH.